1996
DOI: 10.1002/19960401nt6
|View full text |Cite
|
Sign up to set email alerts
|

Response of growing swine to dietary exposure to pure fumonisin B1 during an eight‐week period: Growth and clinical parameters

Abstract: Consumption of corn or corn-based products contaminated with Fusarium moniliforme/fumonisins has been associated with a variety of animal and human diseases and is a major food/feed safety issue. This study focused on the clinical toxicity and performance parameters in growing swing exposed to low to moderate levels of pure fumonisin B1 (FB.) for 8 weeks. Male (castrated) and female pigs were fed diets containing 0,0.1,1.0, and 10 mg FB1/kg diet (ppm). Weight gains and feed consumption were measured weekly. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 41 publications
4
78
0
5
Order By: Relevance
“…In other pigs, the formation of papillary downgrowths of the stratum basale of the distal oesophageal mucosa were observed. Although incidence of PPE has not been reported in other studies (Rotter et al, 1996), increased Sa : So ratios have been observed with fumonisin levels of 10 mg/kg diet. At lower fumonisin levels, erratic feed intake and growth patterns and increased carcass fat content may also occur (Table 4).…”
Section: Porcine Pulmonary Edema (Ppe)mentioning
confidence: 60%
See 1 more Smart Citation
“…In other pigs, the formation of papillary downgrowths of the stratum basale of the distal oesophageal mucosa were observed. Although incidence of PPE has not been reported in other studies (Rotter et al, 1996), increased Sa : So ratios have been observed with fumonisin levels of 10 mg/kg diet. At lower fumonisin levels, erratic feed intake and growth patterns and increased carcass fat content may also occur (Table 4).…”
Section: Porcine Pulmonary Edema (Ppe)mentioning
confidence: 60%
“…The choice of performance and biochemical criteria may also influence selection of tolerance values. For example, Rotter et al (1996) suggested that for FB 1 erratic growth occurred in growing pigs at levels as low as 0.1 mg/kg diet, followed by reduced growth and biochemical abnormalities in blood at 1 mg/kg diet. If sphingolipid aberration in tissues are used as the criterion, then changes would not occur until diets contained 10 mg FB 1 /kg.…”
Section: Advisory and Tolerance Limitsmentioning
confidence: 99%
“…In challenged pigs, the clinical and immunological parameters can also be influenced by sex (Cote et al, 1985;Rotter et al, 1996;Marin et al, 2006). Some authors suggest that the greater susceptibility of males would be related to differences in the mycotoxin hepatic metabolism (Gurtoo and Motycka, 1976;Castegnaro et al, 1998), although this hypothesis needs to be confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…Such clinical signs can develop only after exposure to very high doses of FB 1 such as 100-300 ppm (Harrison et al, 1990;Haschek et al, 1992). However, other studies revealed that dietary exposure of pigs to significantly lower feed levels of FB 1 such as 1-10 ppm, can provoke a partial decrease in body weight gain in the first 4 weeks of life, which can be compensated in a later stage (Rotter et al, 1996). In this regard, our studies support the observations of the authors who observed no visible clinical signs and significant differences in the body weight of the pigs exposed to high levels FB 1 , but it should be taken into account that our levels of FB 1 were significantly lower than the levels used by these authors .…”
Section: Discussionmentioning
confidence: 99%